Numerical determination of the mechanical stiffness of a force measurement device based on capacitive probes: Application to roller bearings. Issue 1 (28th August 2016) - Bogard, Fabien; Murer, Sébastien; Rasolofondraibe, Lanto; Pottier, Bernard
Abstract: Bearings allow external loadings to be transferred from one raceway to the other through rolling elements, which induces strains in the bearing constituents. In order to measure the radial component of these forces, the fixed ring is inserted within a housing equipped with capacitive probes able to measure displacements with very high sensitivity. This work mainly focuses on determining the optimal housing shape using FE simulations and their influence on the global stress state undergone by the structure. Finally, an averaged global stiffness is computed, allowing proper calculation of the contact forces involved in the bearing. Graphical abstract: